PREPARATORY MODULE FOR THE OBJECT-ORIENTED MODELING OF URBAN TERRAIN HYDROLOGICAL RESPONSE - Pah, Jusuf J. S. (Jurnal Teknik Sipil, 2013)
This research aimed at preparing an object-oriented module to use in conjunction with an object-oriented urban terrain hydrological response model. The module serves to capture terrain data and prepare them and make them fit as input to the core part of the urban terrain model. This research had constructed the module. It engages five classes of object, which give it capability to faithfully capturing terrain hydrological features and other relevant data, and arrange them in such a way as to serve as fit input to the core part of the urban terrain model. The module represents an urban terrain by meshing it unto a network of rectangle object elements. In order to overcome edge problems associated with the meshing, utilizing smaller size of elements (hence higher number of elements) and weighted average in terms of ?within a cell contained terrain-sheds areas? were advised. It also strongly encouraged the invention of a more automate ways of terrain data capturing, to replace the manual data entry procedure still utilized in this module.